THE KNOWLEDGE MANAGEMENT ORGANIC AGRICULTURE GROUP IN PHETCHABURI PROVINCE - Singchai, Anuruk (Journal of MCU Nakhondhat, 2023)
The purpose of this research article is to study. Firstly, to study the process of knowledge management of organic farming groups in Phetchaburi Province. and secondly, to study ways to support knowledge management of organic farming groups in Phetchaburi Province. The research methodology was qualitative, a case study with in-depth interviews. Participant observation and non-participant observation from organic agriculture group Ban Rai Makham Ban Lat District, Phetchaburi Province. Collect information from target groups by key information providers including, Group president and group members Ban Rai Makham Ban Lat District, Phetchaburi Province. Consumers of organic products, Phetchaburi provincial government representative Community Development Provincial of Phetchaburi. Agriculture and Cooperatives Provincial of Phetchaburi. local government organization. The study Process Knowledge Management organic agriculture group in Phetchaburi province in the production of organic agricultural products included establishment of community rice centers, resource usage co-management of communities and government organizations, community relationship management through the tradition of welcoming Mae Phosop, and community learning management in the form of big farming groups. The support for study the Knowledge Management organic agriculture group in Phetchaburi province. The development of an information system for organic farming. The Support production and Market, Information system knowledge support. Group Leader Potential Development. Management of organic farming groups. The network of organic farming groups in Phetchaburi Province and the support development of product quality.